Semarang City Development After Local Regulation No. 9 of 2014 on Investment - Abib, Agus Saiful; Astanti, Dhian Indah; Izziyana, Wafda Vivid (Fakultas Syariah INSURI Ponorogo, 2025)
This study examines the effectiveness of Local Regulation No. 9 of 2014 in supporting investment in the development of Semarang City. Using an empirical juridical research method, the study integrates normative legal analysis with empirical data to assess how investment regulation operates in practice. Normatively, the research analyzes the regulation's alignment with Law No. 25 of 2007 on Investment and constitutional principles, particularly those related to economic democracy and social welfare. Empirically, the study relies on secondary data, including investment realization statistics, regional economic indicators, and official policy reports issued by relevant government institutions. The analysis is further strengthened by applying Friedman's legal system theory to evaluate the interaction between legal substance, legal structure, and legal culture in the implementation of investment regulation. The findings suggest that the regulation has contributed to improving the investment climate, enhancing investment realization, and promoting employment and regional economic growth. However, its effectiveness remains influenced by institutional capacity, regulatory consistency, and governance practices. The study concludes that continuous regulatory harmonization, institutional strengthening, and improvements in legal culture are essential to optimize the role of investment regulation in achieving sustainable regional development and public welfare.